Association between serum uric acid with diabetes and other biochemical markers - Alqahtani, Saif Aboud M.; Awan, Zuhier A.; Alasmary, Mohammed Yahia; Al Amoudi, Saeed M. (Journal of family medicine and primary care, 2022)
Objective: This study aimed to decipher the association between serum uric acid (UA) and glycated hemoglobin (HbA1c) in the population from the southern region of Saudi Arabia. Method: In this retrospective cross-sectional investigation, clinical data obtained from the different commercial laboratories in the Asir region of Saudi Arabia were screened over 2 years. Data were analyzed using standard statistical methods. Results: A total of 1984 laboratory investigations with 1215 females (61.2%) and 769 males (38.6%) were included in the data analysis. In our investigation, the prevalence of hyperuricemia in the study population was 53.5% (41.2% females and 12.3% males) and in the diabetic population was 12.7% (9.47% females and 3.23% males), in prediabetics was 12.65% (9.8% females and 2.85% males), respectively. Prediabetic subjects had higher UA levels than people with diabetes or healthy people. Higher UA quartiles were associated with a high level of urea, blood urea nitrogen (BUN) creatinine, HbA1c, fasting blood sugar (FBS), and total cholesterol (TC) (P < 0.05). High UA (OR = 1.33 for diabetes; OR = 2.676 for prediabetes), high BUN (OR = 3.05 for diabetes; OR = 2.293 for prediabetes), high TC (OR = 3.75 for diabetes; OR = 1.098 for prediabetes), and high TG (OR = 2.67 for diabetes; OR = 1.943 for prediabetes) parameters are the most influential risk factor in diabetic and prediabetic patients than the people who have normal UA, BUN, TC, and TG value. Conclusion: High UA levels are significantly associated with prediabetes as defined by HbA1c criteria, indicating that UA has a significant role in the disturbance of glucose metabolism. A significant positive association was observed between dyslipidemia and serum UA in the study population.